Optimizing User Interface of MBKM Information System & Academic Services using Design Thinking Method (Case Study: Tadulako University) - Reinaldy Mansa, Jeremy; Anggun Pratama, Septiano; Wirdayanti, Wirdayanti; Angreni, Dwi Shinta (IAIC Transactions on Sustainable Digital Innovation (ITSDI), 2024)
This study addresses the usability challenges faced by Tadulako University's MBKM & Academic Services Information System (SITAMPAN), developed in response to the Ministry of Education’s Merdeka Belajar - Kampus Merdeka (MBKM) initiative. By applying a structured Design Thinking approach, this research seeks to present a novel solution for enhancing user experience and system usability in educational information systems. Through the System Usability Scale (SUS) and User Experience Questionnaire (UEQ) evaluations, initial findings indicated a low usability score (SUS: 41.75, grade "F"), categorizing the system as a "Detractor" in the Net Promoter Score (NPS) framework. Following the implementation of user centered design improvements, the SUS score increased substantially to 86.25 ("A" grade), with NPS shifting to a "Promoter" classification, while UEQ scores showed marked improvement across all metrics. This study demonstrates the effectiveness of Design Thinking in systematically addressing and optimizing the user experience, providing valuable insights for future information system developments in educational contexts.